Biochemical Composition and Nutritive Value of Common Fish Feed Ingredients of Plant and Animal Origin - P.G., Viswanathan Nair; O., Kavitha; R., Anandan; Mathew, suseela (Fishery Technology, 2025)
Formulated fish feed has a very important role in the field of intensive fish farming. Therefore it is essential to assess biochemical and nutritional composition of the ingredients used in the manufacture of the feed to formulate a feed according to the nutritional requirements of fish. In the present study, an attempt has been made to analyze the biochemical composition of some of the common feed ingredients, of both plant origin (Commercial wheat flour. Wheat gluten. Wheat bran. Commercial maida. Commercial atta, Maize, Maize bran, Soya flour and Rice flour) and animal origin (Indian fish meal, Danish fish meal, Peruvian fish meal and Shrimp head meal). A greater amount of variation was observed in the moisture content among ingredients ranging from 4.8-12.8%. The total protein content except in the case of wheat gluten and soya flour was lower in ingredients from plant sources. The essential amino acid composition was also found to be lower in proteins of plant origin when compared to that of animal proteins. The fatty acid analysis of the feed ingredients showed that the n-3 fatty acids were present in higher concentration in all fishmeals and shrimp head meal as compared to ingredients of plant origin. C16.0, C18SS and Cm were the major fatty acids present in the lipids of the ingredients of plant origin, accounting for more than 80%. In the present study, the notable difference was observed between ingredients of plant and animal origin with respect to the proportion of essential amino acids and n-3 polyunsaturated fatty acids (C j and C22. ) indicating that ingredients of animal origin were superior in nutritional composition as compared to the ingredients derived from plants.